"Making Up for Lost Time": The Transition Experiences of Nontraditional Black Male Undergraduates. Issue 4 (November 2018) - Goings, Ramon B.
This qualitative study investigated the academic and social experiences and life events that propelled 13 Black male nontraditional undergraduates to transition back to college and explored the various programs and institutional agents these men used once on campus. Findings indicated that participant's faced challenges with college as traditional-aged students due to being under and over involved with social activities on campus or choosing to pursue a work career. As a result, participants had either delayed entry into college or dropped out as traditional-aged students. However, participants transitioned back to college due to wanting to make up for not completing their degree earlier in life, needing to increase their employment opportunities, and wanting to prove their doubters wrong. Finally, findings indicated that while the men found support from certain professors on their campuses, there were few targeted programs specifically for nontraditional students on campus. Recommendations on how to support nontraditional Black male students are provided.